Desmoid tumour of the chest wall in paediatric post-operatory of heart transplant - Freitas Filho, Orival de; Nakahira, Evelyn Sue; Schmidt Junior, Aurelino Fernandes; Azeka, Estela; Jatene, Marcelo Biscegli; Pego-Fernardes, Paulo Manuel (Frontiers in Pediatrics, 2022)
Report the first case report of a patient in the postoperative period of heart transplantation who presented with a desmoid tumour (DT). A 13-year-old male had dilated cardiomyopathy which required a cardiac resynchronization device implant three years before. And two years after the device was implanted he had a heart transplant. He presented a progressively growing mass on the generator site in one month, so the decision was to remove the device. During the surgery, there was no haematoma or fluid collection. However, there was a progression of the lesion. The lesion was biopsied and the anatomopathological diagnosis was a desmoid tumour. Resection surgery happened four months after the start of development of the mass that reached 20 centimetres in the largest diameter. The lesion infiltrated the pectoralis major muscle and microscopically did not invade the intercostal muscles or ribs. The pectoralis major was resected partially en bloc with the lesion. The defect had primary closure. The patient evolved without postoperative complications and was discharged on the fourteenth postoperative day. The surgical specimen came with negative circumferential margins, but microscopically positive deep margins. Due to deep involvement, the patient underwent adjuvant radiotherapy two months after surgery. Currently, the patient is under clinical follow-up and has no evidence of tumour recurrence. DT is a rare tumour, with unpredictable courses. Surgery can be considered in the progression of lesions. Treatment is justified by long survival after a heart transplant and in DT patients. DT is a differential diagnosis to be considered in progressive growth lesions.